2020
DOI: 10.1039/d0ra06129h
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, expression, and biochemical characterization: nitrite reductase from Bacillus cereus LJ01

Abstract: Biological remediation of toxic oxygen-containing anions such as nitrite in the environment is of great significance. Bacillus cereus LJ01 showed the activity of degradation for nitrite. the enzyme NiR from LJ01 can degrade the nitrite in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…John et al (2020), for instance, outlined many members of Bacillus including Bacillus cereus and Bacillus amyloliquefaciens to have the capacity to break down nitrite and ammonia. Similarly, Huang et al (2020) reported different strains of Bacillus (Bacillus cereus LJ01) as having the capacity to degrade nitrite due to its ability to synthesize nitrite reductase, an enzyme responsible for nitrite degradations. Accordingly, Song et al (2011) revealed that Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…John et al (2020), for instance, outlined many members of Bacillus including Bacillus cereus and Bacillus amyloliquefaciens to have the capacity to break down nitrite and ammonia. Similarly, Huang et al (2020) reported different strains of Bacillus (Bacillus cereus LJ01) as having the capacity to degrade nitrite due to its ability to synthesize nitrite reductase, an enzyme responsible for nitrite degradations. Accordingly, Song et al (2011) revealed that Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of different nitrite concentrations (0, 100, and 300 mg/L NaNO 2 ) on the growth of L. fermentum RC4 at 8 h were tested by using scanning electron microscopy (SEM) (JSM 6390 LV; JSM, Tokyo, Japan) and surface hydrophobicity (CSH). 7 SEM measurement was operated at 10 kV. Briefly, the pellets of the Control, Nitrite100, and Nitrite300 groups were obtained by centrifugation (8000 rpm, 10 min), washed, and promptly fixed with 2.5% glutaraldehyde, 4 °C for 2 h. Then the cells were washed three times with 0.1 M phosphate buffer saline (PBS, pH 7.2) and dehydrated in a graded ethanol series (30,50,70,80, 95, 100%) each for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of different nitrite concentrations (0, 100, and 300 mg/L NaNO 2 ) on the growth of L. fermentum RC4 at 8 h were tested by using scanning electron microscopy (SEM) (JSM 6390 LV; JSM, Tokyo, Japan) and surface hydrophobicity (CSH) …”
Section: Methodsmentioning
confidence: 99%